EVALUASI KEBIJAKAN PENETAPAN DAN PENEGASAN BATAS DESA DI KABUPATEN KEPULAUAN SANGIHE - Bataha, Katerina; Monintja, Donald K; Anisykurlillah, Rosyidatuzzahro (Dinamika Governance: Jurnal Ilmu Administrasi Negara, 2025)
This study aims to evaluate the policy of determining and affirming village boundaries in Sangihe Islands Regency using the CIPP (Context, Input, Process, Product) approach. This approach is considered relevant to assess public policies, not only in terms of results, but also in the context of the policy, resource readiness, and quality of implementation. This study uses a qualitative method with data collection techniques through in-depth interviews, observations, and documentation studies. The results of the study indicate that, from the context aspect, this policy is very much needed to encourage orderly village governance. So far, the local government has implemented the stipulation of the Regent Regulation regarding the affirmation of village boundaries in 23 villages. Regarding input, existing infrastructure is relatively sufficient, utilizing facilities from the Regional Secretariat’s Governance Division and the Public Works and Spatial Planning Office. The implementation process, however, faces several challenges, including limited human resources and budget constraints within the district government. In terms of product, the results remain suboptimal as many villages still lack clearly defined boundaries. The study recommends that the Ministry of Villages align with the Ministry of Home Affairs to allow the use of village funds for boundary affirmation. Additionally, provincial governments should play a more active role in supervising their respective areas and serve as communication/coordination bridges between regencies/municipalities and the Ministry of Home Affairs and the Geospatial Information Agency (BIG). Technical guidance and verification of mapping personnel by BIG can be facilitated at the provincial level.